The genus Miconia (Melastomataceae) in Espírito Santo, Brazil - Bacci, Lucas F.; Caddah, Mayara K.; Goldenberg, Renato (Phytotaxa, 2016)
Miconia is the largest genus of Melastomataceae in Brazil with more than 280 species, of which 120 are found in the Atlantic Rainforest. We present here a taxonomic treatment for the species of Miconia that occur in Espírito Santo, with morphological descriptions, geographic distribution, comments, photos and an identification key. We found 55 species, from which six were recently described (five endemic, M. capixaba, M. kollmannii, M. michelangeliana, M. ruschiana and M. valentinensis, and one with wider distribution, M. atlantica) and six are new records for the state (Miconia molesta, M. petroniana, M. staminea, M. stenostachya, M. valtheri and M. willdenowii). One species is presented here as a new species that will be described soon by other authors.